2000
DOI: 10.1006/dbio.2000.9794
|View full text |Cite
|
Sign up to set email alerts
|

Development and Control of Tissue Separation at Gastrulation in Xenopus

Abstract: During Xenopus gastrulation, the internalizing mesendodermal cell mass is brought into contact with the multilayered blastocoel roof. The two tissues do not fuse, but remain separated by the cleft of Brachet. This maintenance of a stable interface is a precondition for the movement of the two tissues past each other. We show that separation behavior, i.e., the property of internalized cells to remain on the surface of the blastocoel roof substratum, spreads before and during gastrulation from the vegetal endod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 44 publications
2
94
1
Order By: Relevance
“…This gene was included in our study for its known cooperation with Gsc in the control of motility-related properties (Wacker et al, 1998(Wacker et al, , 2000. We showed that Mix.1 acts as a com- Kreyszig, 1973; as in Fig.…”
Section: Cell Motility In the Vegetal Domainmentioning
confidence: 79%
See 1 more Smart Citation
“…This gene was included in our study for its known cooperation with Gsc in the control of motility-related properties (Wacker et al, 1998(Wacker et al, , 2000. We showed that Mix.1 acts as a com- Kreyszig, 1973; as in Fig.…”
Section: Cell Motility In the Vegetal Domainmentioning
confidence: 79%
“…2D), suggesting that Mix.1 is also necessary for rapid migration, and functions in this context as a repressor. Collaboration of Gsc and Mix.1 as repressors has previously been shown for the control of tissue separation in the HM (Wacker et al, 2000).…”
Section: Gsc Cooperates With Mix1 and Sia To Promote Rapid Hm Cell Mmentioning
confidence: 91%
“…The ability of the cells to migrate across adjacent cells towards a sf-PDGF-A source was directly demonstrated in vitro. The PCM is separated from the ectodermal BCR by Brachet's cleft, a tissue boundary maintained by cycles of attachment and repulsion between ectoderm and mesoderm cells (Wacker et al, 2000) (N. Rohani, L. Canty, O. Luu, F. Fagotto and R.W., unpublished). The resulting dynamic adhesion between germ layers ensures that while the PCM cells can move across the BCR, they cannot penetrate into it despite being attracted by sf-PDGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…During Xenopus and zebrafish gastrulation, the over or underexpression of paraxial protocadherin (papc) leads to defects in convergence and extension of the forming embryonic body axis (Hukriede et al, 2003;Kim et al, 1998;Yamamoto et al, 1998). Furthermore, when XB/U-or EP/C-Cadherin function is blocked at the onset of Xenopus gastrulation, both mesodermal progenitor cell involution and migration, as well as germ layer separation, are affected (Kuhl et al, 1996;Lee and Gumbiner, 1995;Wacker et al, 2000). Finally, inactivating E-Cadherin in Xenopus and zebrafish embryos causes variable defects before and during gastrulation, including impaired prechordal plate formation and migration in zebrafish and ectodermal lesions in Xenopus (Babb and Marrs, 2004;Levine et al, 1994).…”
Section: Introductionmentioning
confidence: 99%